New Schmitt Trigger with Controllable Hysteresis using Dual Control Gate-Floating Gate Transistor (DCG-FGT) - Abderrezak Marzaki; V. Bidal; R. Laffont; W. Rahajandraibe; J-M. Portal; R. Bouchakour (International Journal of Reconfigurable and Embedded Systems (IJRES), 2013)
This paper presents different low voltage adjustable CMOS Schmitt trigger using DCG-FGT transistor. Simple circuits are introduced to provide flexibility to program the hysteresic threshold in this paper. The hysteresis can be controlled accurately at a large voltage range. The proposed Schmitt trigger have been designed using 90nm 1.2V CMOS technology and simulated using Eldo with PSP device models. The simulation results show rail-to-rail operation and adjustable switching voltages VTH- (low switching voltage) and VTH+ (high switching voltage).